2018
DOI: 10.1002/pits.22135
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and hindrance stress among schoolteachers

Abstract: The challenge–hindrance stress framework argues that certain job stressors have entirely detrimental effects (hindrance stress), but some may also have beneficial effects (challenge stress). Though the challenge–hindrance framework has largely been neglected in teacher stress research, we adopted it to provide a more differentiated view of the most prominent stressors in the teaching profession. We asked a sample of 528 secondary schoolteachers to report the extent to which they perceived occupation‐specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
(103 reference statements)
0
13
0
Order By: Relevance
“…Both approaches have been used, and the issue of measurement is that studies have found interesting results 1 , with support for both measuring appraisals directly (e.g., Searle & Auton, 2015;Stiglbauer & Zuber, 2018) or as rated by expert coders (e.g., Cavanaugh et al, 2000;Crawford, LePine, & Rich, 2010;LePine et al, 2005). From the resource approach, appraisals may not matter very much if it is reasonable to assume that most employees appraise job demands as challenging and work overload as hindering.…”
Section: Original Theoretical Background: Resources And/or Appraisalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both approaches have been used, and the issue of measurement is that studies have found interesting results 1 , with support for both measuring appraisals directly (e.g., Searle & Auton, 2015;Stiglbauer & Zuber, 2018) or as rated by expert coders (e.g., Cavanaugh et al, 2000;Crawford, LePine, & Rich, 2010;LePine et al, 2005). From the resource approach, appraisals may not matter very much if it is reasonable to assume that most employees appraise job demands as challenging and work overload as hindering.…”
Section: Original Theoretical Background: Resources And/or Appraisalsmentioning
confidence: 99%
“…But the employees' appraisals of them as some degree of challenge and hindrance might help our research, theorizing, and practice. For example, one study used data collected from 582 schoolteachers who rated 15 stressors as challenges and also as hindrances (Stiglbauer & Zuber, ). They found that stressors appraised more as hindrances were related to more strains (e.g., fatigue, tension, cardiovascular distress, musculoskeletal disorders, and digestive complaints) than were challenge appraisals.…”
Section: Original Theoretical Background: Resources And/or Appraisalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cruwys et al (2014) revealed that a better level of social identification along with physical and emotional well-being is reached due to challenge stress. Stiglbauer and Zuber (2018) emphasized that management of stress is essential for organizations as well as for individuals, which helps to moderate the consequences of stress by assembling capabilities at a personal level. This finding is also discussed by Wang et al (2017), which strengthens the evidence that challenge stressors are imperative to formulate different identities.…”
Section: The Relationship Between Challenge Stressors and Identity Ormentioning
confidence: 99%
“…Second, drawing on the broaden-andbuild theory (Fredrickson, 2001), the current study augments the emergent literature on identity orientation by justifying challenge stressors as its antecedent. Theoretically, in the previous literature, the concept of challenge stressors has been widely supported by transactional stress theory (Salanova et al, 2011;Amah, 2014;Stiglbauer and Zuber, 2018) and the conservation of resource theory (Hobfoll, 1989(Hobfoll, , 2012Hobfoll et al, 2012Hobfoll et al, , 2018. However, the mechanism which relates challenge stressors to the particular identity is still under-discussed.…”
Section: Introductionmentioning
confidence: 99%